The Transmitter's 'Adalah (Uprightness); The Ethical Conception in the Hadith Transmission - Budiman, Arif (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2022)
A transmitter as the main element in the hadith transmission has special conditions. It relates to considerations in determining the hadith qualifications. One of the conditions playing a central role is the transmitter's uprightness ('adalah). The article aims to reveal that the transmitter's uprightness intersects with ethical philosophy. As a prescriptive science, ethics is a branch of philosophy that considers an action critically with certain moral parameters. Through a qualitative study using the moral philosophy approach from the perspective of Agus Dewantara, the transmitter's uprightness conception correlates with ethical values. As A result, the transmitter's uprightness has two ethical dimensions. First, the ethical-theological dimension correlates with subjective moral order including: a transmitter must have a Muslim identity and implement religious provisions. Second, the ethical-sociological dimension correlates with an objective moral order meaning that a transmitter must be mukallaf and always maintain self-image (muru'ah).